Kajian Teologis Tentang Kepemimpinan Yang Berintegritas Serta Relevansinya Bagi Gereja Masa Kini - Tafonao, Yaasokhi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2024)
This study discusses the importance of integrity in church leadership and its impact on congregational trust, morality, and spiritual development. The main focus is understanding the essence of church leadership with integrity through analyzing biblical texts, Christian ethics, and spiritual values in Christian teachings. This research aims to identify the theological foundation that depicts honest leadership and explore its application to the contemporary church. The research method used is a literature review. The findings indicate that integrity is a primary aspect of successful church leadership. Leaders with integrity reflect the character of Christ, adhere to moral and spiritual values, and positively impact the congregation's spiritual growth. However, maintaining integrity amidst modern dynamics is a challenge that requires wise adaptation. In conclusion, integrity in church leadership is a crucial element for spiritual growth and congregational unity. Church leaders with integrity can maintain unity and trust and face modern challenges wisely, contributing valuable insights to developing relevant and effective church leadership models.